Clinical Studies with Bismuth-213 and Actinium-225 for Hematologic Malignancies - Jurcic, Joseph G. (Current Radiopharmaceuticals, 2018)
Objectives: Due to the shorter range and higher linear energy transfer of α-particles compared to β-particles, targeted α-particle therapy may produce more efficient tumor killing while sparing neighboring healthy cells. We will review the clinical studies using α-particle therapy for Acute Myeloid Leukemia (AML). Methods: A series of clinical trials were conducted to assess the safety, feasibility, and anti-leukemic effects of lintuzumab, an anti-CD33 humanized monoclonal antibody, labeled with the α-emitters bismuth- 213 (213Bi) and actinium-225 (225Ac). Results: An initial phase I study conducted in 18 patients with relapsed or refractory AML demonstrated the safety and antitumor effects of 213Bi-lintuzumab. Subsequently, 213Bi-lintuzumab produced remissions in AML patients after partial cytoreduction with cytarabine in phase I/II trial. The 46- minute half-life of 213Bi and need for an onsite generator has limited its utility. Therefore, a secondgeneration construct was developed using 225Ac, a radiometal that yields four α-particle emissions. A phase I trial demonstrated that a single infusion of 225Ac-lintuzumab could be given safely at doses up to 111 kBq/kg with anti-leukemic activity across all dose levels studied. In a second phase I study, 28% of older patients with untreated AML had objective responses after receiving fractionated-dose 225Aclintuzumab and low-dose cytarabine. Conclusion: Based upon the encouraging results seen in phase I trials of 225Ac-lintuzumab, a phase II study of 225Ac-lintuzumab monotherapy for older patients with untreated AML is now in progress and is also being studied in a subset of patients with CD33-positive multiple myeloma.
Keywords: alpha-particle